2018
DOI: 10.4102/sajcd.v65i1.582
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of asynchronous telehealth-based hearing screening and diagnostic services using automated audiometry in a rural South African school

Abstract: BackgroundAsynchronous automated telehealth-based hearing screening and diagnostic testing can be used within the rural school context to identify and confirm hearing loss.ObjectiveThe aims of the study were to evaluate the efficacy of an asynchronous telehealth-based service delivery model using automated technology for screening and diagnostic testing as well as to describe the prevalence, type and degree of hearing loss.MethodA comparative within-subject design was used. Frequency distributions, sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Feder et al (2017) found that 7.7% of Canadian children aged 6-19 had HL at one or more pure-tone frequencies. Govender and Mars (2018) assessed 146 ears and found that 23 ears of 20 children (16%) presented with hearing loss. In rural areas of Poland, the rate of positive results of hearing screening was 16.4% (Skarżyński et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Feder et al (2017) found that 7.7% of Canadian children aged 6-19 had HL at one or more pure-tone frequencies. Govender and Mars (2018) assessed 146 ears and found that 23 ears of 20 children (16%) presented with hearing loss. In rural areas of Poland, the rate of positive results of hearing screening was 16.4% (Skarżyński et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of telepractice are well-documented across both education and allied health (Keck andDoarn 2014, Valentine et al 2021). These benefits include increased service availability, convenience, improved caseload management resulting in more costeffective service delivery, improved access to services for people living in rural and remote areas (Fairweather et al 2016); and removal of travel and geographical barriers (Govender andMars 2018, Yoo et al 2020). Telepractice has facilitated access to education for students who are unable to attend full-time classes (Burdina et al 2019) and has a long history through Distance Learning programs (Cavanaugh et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These benefits include increased service availability, convenience, improved caseload management resulting in more cost‐effective service delivery, improved access to services for people living in rural and remote areas (Fairweather et al . 2016); and removal of travel and geographical barriers (Govender and Mars 2018, Yoo et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tele-audiology rehabilitative studies designed for hearing aid users have consistently shown positive consequences, including improved hearing aid satisfaction and improved quality of life for patients (e.g. Gomez and Ferguson 2020;Thor en et al 2014). Clinicians implementing remote rehabilitation services may consider including the following elements; (a) providing engaging education materials related to hearing loss and self-management of hearing aids/assistive listening devices, (b) strategies to help adjust to new hearing-aids and (c) online support groups for first time hearing aid users.…”
Section: Discussionmentioning
confidence: 99%